IMPLEMENTASI PERATURAN GUBERNUR BANTEN NOMOR 74 TAHUN 2014 TENTANG PEDOMAN PENYELENGGARAAN PENDIDIKAN INKLUSIF DI PROVINSI BANTEN (STUDI PADA SEKOLAH INKLUSIF DI KOTA SERANG) - Titi Stiawati Titi Stiawati; Listyaningsih Listyaningsih; Syarifah Rahmi Aziizi (Universitas Sultan Ageng Tirtayasa, 2017)
The existence of Inclusive Education in Indonesia is still very foreign to the general public. Thus with Inclusive Education in Serang City is still in a state of minimal attention from the City Government Attack Serang City Office of Education and Culture. The achievement of the objectives of the Banten Governor Regulation no. 74 of 2014 to realize education that values diversity and non-discrimination for all learners well in Serang City, the unavailability of special facilities and infrastructure in inclusive schools in Serang City, and the shortage of Special Supervisor Teachers In inclusive schools in Serang City is the concern why This study was conducted. This research is aimed to know and analyze how the implementation of Guidance of Implementation of Inclusive Education to be done by Education and Culture Office of Serang City. The theory used is the theory of Public Policy Implementation George Edward III in Agustino (2006: 149). This research uses qualitative approach with descriptive method. Data analysis technique used is Miles & Huberman model. The result of this research shows that the implementation done by the Education and Culture Office of Serang City in implementing the Inclusive Education has not been implemented optimally. Due to the proper Implementation to be implemented, it is necessary to do in Bureaucracy structure which will then have an effect on the clear communication between the implementer and the Responsible Resource needed in the implementation of the policy and the disposition of equal distribution of responsibility.